RESEARCH ON THE TRENDS IN MILK PRODUCTION AND CONSUMPTION IN ROMANIA - Agatha POPESCU (Scientific Papers Series : Management, Economic Engineering in Agriculture and Rural Development, 2015)
The purpose of the paper was to analyze the main trends in the milk and dairy products market in Romania in the period 2007-2012 and to set up the forecast for the 2013-2015 horizon, based on the empirical data provided by the National Institute of Statistics and Eurostat and using the fixed basis index, average change method, and comparison method. Milk production for consumption reached 210 thou tons in 2012 registering a descending trend. Despite that milk production decreased in the period 2007-2012, the production diversification applied by dairies supported the growth of dairy products output as follows: by 13.54 % for milk, by 3.45 % for sour cream, and by 13 % for butter. The forecast for the year 2015 provides that the production of dairy products will account for: 223,936.6 tons milk for consumption, 48,709.4 tons sour cream, 166,674.2 tons acidulated milk, 9,937.6 tons butter and 66,584.4 tons cheese. The development of milk processing imposes the improvement of production technologies, products quality, efficiency and competitiveness. Due to the unbalanced demand/offer ratio, after the elimination of milk quota, the Romanian milk and dairy products market will be invaded by foreign products.